Report from the 8th International Conference Early Childhood Care and Education ECCE, Moscow (Russia), 29th of May – 1st of June 2019 - Adamczewski, Jakub (Studia Edukacyjne, 2019)
Report from the 8th International Conference Early Childhood Care and Education ECCE, Moscow (Russia), 29th of May – 1st of June 2019